Integrated micro-ring photonics : principles and applications as slow light devices, soliton generation and optical transmission /: principles and applications as slow light devices, soliton generation and optical transmission. (2017) - Amiri, Iraj Sadegh, 1977-; Afreezeh, Abdolkarim; Ahmad, Hatith
No abstract available